ANALISIS TENTANG PENGARUH MOTIVASI DAN MINAT TERHADAP SIKAP UNTUK BERWIRAUSAHA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI IKIP PGRI MADIUN - M.Th. Kuswariningsih (Universitas PGRI Madiun, 2014)
An individual has a driving factor either consciously or unconsciously , it is motivation . Once a person experiences a state that encourages behavior toward a goal, then the resulting realization that an object , or something about the situation contained nothing to do with him . Thus the individual has an interest which is welcome consciously , because if not so then interest has no meaning at all . With the motivation of the individual self and the interest in entrepreneurship began to determine the attitude of an individual that is a typical way of behaving that is focused on specific issues , which in this case is self-employed . This study aims to determine motivation, interest, attitude of students of entrepreneurship on Economics Education Program at IKIP PGRI Madiun and the influence of motivation and interest in the attitude of students of entrepreneurship on Economic Education Teachers' Training College PGRI Madiun. The population in this study were 100 students with a sample of 30 students with a sampling technique that is purposive sampling . Techniques of data collection obtained by using questionnaires and documentation . Hypothesis was tested using multiple linear regression , the F test and t test. . The results of this study are ) students who have very good motivation as much as 1 or 3.33 % , (b ) students who have a good motivation as many as 8 people , or 26.67 % , (c ) students who have a good enough motivation as many as 13 people or 43.33 (d ) students who are less well motivated as much 7orang or 23.33 % , and ( e ) students who have a very poor motivation as much as 1 or 3.33 % , while students who have an interest in very good as much as 1 or 3.33 % , (b ) a student who has an interest either as many as 12 people or 40.00 % , (c ) students who have an interest in good enough as many as 11 people or 36.67 (d ) students who have unfavorable interest as much as 3 or 10.00 % , and ( e ) students who have an interest in very poor as many as 3 people or 10.00 % of the test proved that the correlation value is 0.973 while the value rhit rtab with a significance level of 5 % with N 30 at 0,361 . This means that rhit ≥ rtabel ( 0.973 ≥ 0.361 ) . This situation can be said that the H0 is rejected and Ha accepted means there is a relationship of motivation and interest in entrepreneurship attitude . On the other hand , if viewed from the determination or donation motivation and interest in entrepreneurship attitude is that the magnitude of the value of R2 . or R sequare of 0.947 which means donations motivation and interest in entrepreneurship attitude was 97.70 % , while the remaining 2.30 % is influenced by other factors Of the F test , proved that the F value ≥ Ftable ( 240.667 ≥ 5.49 ) or ≤ Sighit Sigprob ( 0.000 ≤ 0.05 ) . Fhit value at 5% significance level with df 2 and 27 residues of 5.49 . overall means of motivation and interest in entrepreneurship affect the entrepreneurial attitude. . . From the equation Y = 2,514 + 0.745 X1 - 0.086 X2 . If motivation is increased by 1 % , and an increase in entrepreneurship attitude of 0.745 % , when other factors are considered constant . If the interest is increased by 1 % , will decrease by 0.086 % entrepreneurial attitude when other factors are considered constant . In the t test derived from motivational variables thit value is 20.670 while the value ttabel at significance level of 5 % and at DK = NK = 27 at 2,052 , this means thitu ≥ ttab ( ≥ 20.670 2.052 ) means that there are different motivational variables influence the entrepreneurial attitude . Of the t test , the variable interest thit value obtained is -2.050 while the value ttabel at significance level of 5 % and DK = NK = 27 at 2,052 , this means thitu ttab ( -2.050 2.052 ) difference means no influence interest in entrepreneurship attitude . This study therefore concluded that there are significant between motivation and interest in student attitudes to entrepreneurship on Economics Education Program at IKIP PGRI Madiun.